Tying the Knot: The Importance of Financial Literacy Education in Maine - Leach, David (Maine Policy Review, 2016)
David Leach discusses the importance of financial literacy and describes the Downeaster Consumer Guides, a series of publications on credit cards, debt collection, auto buying and financing, credit reports and scores, home buying and financing, consumer scams, student loans, consumer credit, elder financial protection, and high-interest loans published by Bureau of Consumer Credit Protection.
Keywords: financial literacy; Maine; Downeaster Consumer Guides